SELF EFFICACY SEBAGAI MEDIATOR PADA HUBUNGAN GAYA IDENTITAS DENGAN ACADEMIC BUOYANCY - Fifih Nurafifah; Gagan Hartana; Linda Primana (Psympathic : Jurnal Ilmiah Psikologi, 2012)
Student anxiety facing national exam describes that they have academic buoyancy.  Research from Jakubowski & Dembo (2004), Hejazi, Shahraray, Farsinejad, & As-gari (2009) shows that identity model correlate with self efficacy. Besides, Martin & Marsh (2002, 2008), Martin, Colmar & Davey (2010), concluded from their research that self efficacy correlate with academic buoyancy. Therefore, based on those two researches and mediated model from Baron and Kenny (1986), self efficacy assumed be able to have a role as mediator in identity model and academic buoyancy correlation. This research involved 200 students grade XII from five schools in Bandung. Instruments used are identity model self efficacy, and academic buoyancy questionnaire. Data was analised using path analysis. Result shows that self efficacy has a role as mediator in correlation of informational identity model, normative identity model and academic buoyancy. In addtion, diffuse / avoidant identity model correlated with academic buoyancy without mediated by self efficacy. Commitment is also found correlated with academic buoyancy without mediated by self efficacy.